Stromal epigenetic alterations drive metabolic and neuroendocrine prostate cancer reprogramming - Mishra, Rajeev; Haldar, Subhash; Placencio, Veronica; Madhav, Anisha; Rohena-Rivera, Krizia; Agarwal, Priyanka; Duong, Frank; Angara, Bryan; Tripathi, Manisha; Liu, Zhenqiu; Gottlieb, Roberta A.; Wagner, Shawn; et al. (The Journal of clinical investigation, 2018)
Prostate cancer is an androgen-dependent disease subject to interactions between the tumor epithelium and its microenvironment. Here, we found that epigenetic changes in prostatic cancer-associated fibroblasts (CAF) initiated a cascade of stromal-epithelial interactions. This facilitated lethal prostate cancer growth and development of resistance to androgen signaling deprivation therapy (ADT). We identified a Ras inhibitor, RASAL3, as epigenetically silenced in human prostatic CAF, leading to oncogenic Ras activity driving macropinocytosis-mediated glutamine synthesis. Interestingly, ADT further promoted RASAL3 epigenetic silencing and glutamine secretion by prostatic fibroblasts. In an orthotopic xenograft model, subsequent inhibition of macropinocytosis and glutamine transport resulted in antitumor effects. Stromal glutamine served as a source of energy through anaplerosis and as a mediator of neuroendocrine differentiation for prostate adenocarcinoma. Antagonizing the uptake of glutamine restored sensitivity to ADT in a castration-resistant xenograft model. In validating these findings, we found that prostate cancer patients on ADT with therapeutic resistance had elevated blood glutamine levels compared with those with therapeutically responsive disease (odds ratio = 7.451, P = 0.02). Identification of epigenetic regulation of Ras activity in prostatic CAF revealed RASAL3 as a sensor for metabolic and neuroendocrine reprogramming in prostate cancer patients failing ADT.